Student projects in environmental science - Harrad, Stuart, 1962-; Arhonditsis, George, ....-; Batty, Lesley, ....- (Chichester : Wiley, 2008)
Research projects are among the core components of many undergraduate and Masters degrees within environmental science and physical geography, and students increasingly undertake courses in quantitative research methodology before starting on their own assignment. This one-stop-shop text guides students through their research project from the initial stages of choosing a suitable topic, of conducting the relevant experiments and interpreting the data, through to effective presentation of the results. Takes a case-study approach to illustrate the range of environmental science topics, with cases supplied by specialists in the field. Practical worked examples and self-assessment tasks illustrate key statistical and mathematical points so as to keep heavy theory to a minimum Covers software such as Excel, SPSS and mathematical modelling, and includes statistical tables
Keywords: Environmental Sciences and Forestry. Environmental Sciences -- Environmental Sciences (General).